The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/eihsc-10-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Pacific peoples, mental health service engagement and suicide prevention in Aotearoa New Zealand

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Countries in the Pacific Region, including Samoa, experienced epidemic youth suicide rates between 1960 to 1995 with a peak in 1980 [ 30 ]. High suicide rates in Samoa continued until 2013 despite significant investments in prevention programs [ 31 ]. More recent estimates from Samoa (2016) show a 20–40% decrease of adult suicide mortality attributed largely to the success in a ban on lethal pesticides like paraquat [ 4 , 32 – 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Countries in the Pacific Region, including Samoa, experienced epidemic youth suicide rates between 1960 to 1995 with a peak in 1980 [ 30 ]. High suicide rates in Samoa continued until 2013 despite significant investments in prevention programs [ 31 ]. More recent estimates from Samoa (2016) show a 20–40% decrease of adult suicide mortality attributed largely to the success in a ban on lethal pesticides like paraquat [ 4 , 32 – 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research mirrors others who have found that Pasifika people are more likely to access services which consider different cultural perspectives and seek to deliver more holistic care. 23,24,25 Official resettlement support programmes could include discussions of mental health issues and support. This would help newly arriving families know what to expect from acculturation and where to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…Department of Health and Human Services, 2001). Previous work has demonstrated that Pacific mental health beliefs can differ from Western beliefs due to their contrasting perspectives regarding mental distress, cultural identity, and social and familial connection and obligation (Canfield & Cunningham, 2004;Culbertson, 1999;Hezel, 1994;Tiatia-Seath, 2014;Vaioleti, 2006;Vaka, 2014). Higher rates of mental distress among Pacific populations in NZ may reflect greater barriers to accessing mental health services, greater burden of economic inequality and cultural differences in mental health beliefs.…”
Section: Pasifika In New Zealandmentioning
confidence: 99%